Police spokespersons: A question of organizational representation. (September 2020) - Simpson, Rylan; Wetherell, Kamali'ilani
Police spokespersons exist at the core of organizational representation: they are selected to represent their agencies at all levels of engagement on all public platforms. Given their repeated exposure via traditional and electronic media, perceptions of spokesperson characteristics may impact perceptions of police and police organizations more broadly. Using online search queries of publicly available sources, we collected data for 612 spokespersons from 514 municipal police agencies across the United States. Our analyses reveal that spokespersons are overwhelmingly sworn, White men who are middle-aged and mid-rank. Our analyses also reveal some bivariate relationships between spokesperson characteristics (e.g., gender and employment status) and some variation among characteristics across states (e.g., Texas versus Ohio). By identifying and describing spokesperson characteristics at both national and state levels, we extend historical research regarding police spokespersons, contribute to the scholarly understanding of police representation practices, and theorize the relationships between spokespersons, organizations, and contemporary policing issues.